Measuring the coolness of interactive products: the COOL questionnaire. Issue 3 (3rd March 2016) - Bruun, Anders; Raptis, Dimitrios; Kjeldskov, Jesper; Skov, Mikael B.
ABSTRACT: Coolness has recently started to be explored as a design goal for interactive products from practitioners as well as researchers within human–computer interaction (HCI), but there is still a need to further operationalise the concept and explore how we can measure it. Our contribution in this paper is the COOL questionnaire. We based the creation of the questionnaire on literature suggesting that perceived coolness is decomposed to outer cool (the style of a product) and inner cool (the personality characteristics assigned to it). In this paper, we focused on inner cool, and we identified 11 inner cool characteristics. These were used to create an initial pool of question items and 2236 participants were asked to assess 16 mobile devices. By performing exploratory and confirmatory factor analyses, we identified three factors that can measure the perceived inner coolness of interactive products: desirability, rebelliousness and usability. These factors and their underlying 16 question items comprise the COOL questionnaire. The whole process of creating the questionnaire is presented in detail in this paper and we conclude by discussing our work against related work on coolness and HCI.